THE EFFECT OF PRODUCT QUALITY, SALES PROMOTION AND SOCIAL INFLUENCE ON CUSTOMER PURCHASE INTENTION IN BELLAGIO SHOES STORE IN MANADO - Walintukan, Cynthia .; Tumbuan, Willem J. F. A.; Tulung, Joy Elly (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: People in Manado always pay attention of their style in fashion especially women. Shoes is one of the important things that woman want. A good quality product, an affordable price and what people think about the product are some factors that woman have to know when they buy a product. Bellagio is one of shoes store that produce good quality product and many kind of promotion has offered in that store. The purpose of this study is to examine the impact of brand equity on consumer purchase intention. A sample of 60 questionnaires were distributed to the customer of Bellagio Shoes Store in Manado, and multiple regression analysis was used. The findings of this research shows that simultaneously the variables product quality, sales promotion and social influence has a signicant effect on customer purchase intention. While partially only quality sales promortion and social influence has significant effect on customer purchase intention, whereas product quality does not have any significant effect on customer purchase intention. Therefore, Bellagio Shoe Store must maintain their sales promotion because this is one factor to attract customers' purchase intentions.Â Keywords : product quality, sales promotion, social influence, purchase intention